2013
DOI: 10.1097/cmr.0b013e32835d5d6f
|View full text |Cite
|
Sign up to set email alerts
|

JARID1B expression in human melanoma and benign melanocytic skin lesions

Abstract: It has been suggested that dynamically regulated expression of the JARID1B protein is required for the continuous growth of tumors and at the same time downregulated in melanoma. The majority of the data on a role of JARID1B in maintaining tumor growth has come from in-vitro and xenografting experiments, with only one immunohistochemical study involving human tissues. We compared JARID1B expression levels in human melanomas and benign nevi and analyzed patterns of spatial distributions of positive cells among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
1
12
1
Order By: Relevance
“…Among the 167 genes that were up‐regulated in PM compared to MN, we found a high overlap with previously reported genes, e.g. PRAME, SSP1 (13,14), CXCL9, PHACTR1, CITED‐1, BCL2A1 (13,15) S100A9, MMP1, FN1 (16), NNMT, SERPIN A3 (13), MCAM (17), ISG15 (18), CDK‐2, and CDK‐4 (19), GDF15 (13,15,20) and Hey1 (15,16). Comparing genes that were down‐regulated from PM to MN with previous studies, we found consensus for CIRBP, FEZ1, PPP1R3C, LDOC1, TRPM1 (16), Desmoglein (17), KRT‐15 (13), FABP7 (20), p57KIP2 and CDKN1 (21).…”
Section: Resultssupporting
confidence: 61%
“…Among the 167 genes that were up‐regulated in PM compared to MN, we found a high overlap with previously reported genes, e.g. PRAME, SSP1 (13,14), CXCL9, PHACTR1, CITED‐1, BCL2A1 (13,15) S100A9, MMP1, FN1 (16), NNMT, SERPIN A3 (13), MCAM (17), ISG15 (18), CDK‐2, and CDK‐4 (19), GDF15 (13,15,20) and Hey1 (15,16). Comparing genes that were down‐regulated from PM to MN with previous studies, we found consensus for CIRBP, FEZ1, PPP1R3C, LDOC1, TRPM1 (16), Desmoglein (17), KRT‐15 (13), FABP7 (20), p57KIP2 and CDKN1 (21).…”
Section: Resultssupporting
confidence: 61%
“…The putative role of JARID1B as an oncogene in cancer development is supported by the observations that JARID1B is highly expressed in prostate cancer and other malignant tumors relative to normal tissues [ 12 , 23 , 32 , 13 ]. The fact that JARID1B as a demethylase capable of removing three methyl groups from histone H3 lysine 4, subsequently downregulation several well-known tumor suppressor genes [ 27 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 96%
“…JARID1B ( KDM5B ) is expressed at higher levels in melanoma than nevi, 143 and has been shown to be required for continuous growth of melanoma in experimental models. 144,145 SETDB1 is a methyltransferase responsible for H3K9me3 methylation (as seen in SAHF) that interestingly has actually been shown to be recurrently amplified in melanoma.…”
Section: Mechanisms Of Growth Arrestmentioning
confidence: 99%